Primary diffuse large B-cell lymphoma of the sigmoid colon. (October 2021) - Erginoz, Ergin; Askar, Ahmet; Cavus, Gokce Hande; Velidedeoglu, Mehmet
Abstract: Introduction: Extranodal lymphomas are commonly encountered in the gastrointestinal tract but lymphomas of colon and rectum are rare. Non-Hodgkin lymphoma is the most common type of colonic lymphoma and represents less than 0.5% of colorectal neoplasms. Chemotherapeutical agents are gateway to disease remission and sometimes cure in most patients but surgery may be necessary in emergent situations. Case presentation: A 77-year-old male patient presented with abdominal discomfort, constipation, and obstructive defecation symptoms. Radiological imaging revealed a mass in the sigmoid colon extending towards the rectum. Colonoscopy was performed and biopsy of a nearly 10 cm ulcerovegetative lesion was obtained. Histological examination following biopsy revealed it to be a diffuse large B-cell lymphoma of the sigmoid colon. There was no indication for surgery and the patient was referred to medical oncology clinic for chemotherapy treatment. Discussion: Non-Hodgkin lymphoma is a lymphoproliferative disorder with the diffuse large B cell lymphoma (DLBCL) being the most common subtype. The DLBCL subtype is rarely observed in the colon and rectum. Chromosomal abnormalities are involved in the pathophysiology and gene rearrangements lead to adjustments in lymphocyte function and differentiation. Conclusion: In this case report, we present a rare presentation of a Non-Hodgkin lymphoma presenting in the sigmoid colon. The disease can present with nonspecific symptoms and various imaging modalities along with histopathological evaluation is necessary for the correct subtyping of lymphoma. Chemoradiotherapy is key for treatment, and surgery is usually reserved for cases of obstruction, perforation, or bleeding. Highlights: Non-Hodgkin lymphoma is the most common type of colonic lymphoma. Extranodal lymphomas of the colon and rectum are rare. Histopathological evaluation is important for subtyping of lymphoma. Chemotherapy is the main form of treatment but sometimes surgery is required.